Report of the Working Group on Agricultural Statistics for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The Working Group on Agricultural Statistics for the Tenth Five-Year Plan (2002-2007) evaluated India’s agricultural data systems to improve reliability, timeliness, and analytical capacity. The report highlights recommendations for better coordination among statistical schemes, strengthening the institutional framework of the Directorate of Economics & Statistics (DES), modernization of crop forecasting using remote sensing technology, and improvements in the Timely Reporting Scheme (TRS), Horticultural Statistics, Crop Cutting Experiments (CCE), and Agricultural Census. Emphasis was placed on enhancing market intelligence, cost of cultivation surveys, and professional capacity building within DES. The report also proposes the FASAL project, a phased initiative to integrate satellite, agro-meteorological, and land-based data for accurate crop forecasting. Collectively, the recommendations aim to ensure robust agricultural statistics, support effective policy-making, enhance food security, and promote sustainable agricultural development in India.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Agricultural Statistics; Tenth Five Year Plan; Crop Forecasting; Directorate of Economics & Statistics; Timely Reporting Scheme; FASAL Project; Agricultural Census; Crop Cutting Experiments; Market Intelligence; Remote Sensing Technology